2015
DOI: 10.1007/s40195-015-0228-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Corrosion and Tribo-Mechanical Properties of Co-deposited Zn–SnO2 Composite Coating

Abstract: Zn-SnO 2 composite coatings were prepared by direct potential using electrolytic co-deposition technique from sulfate solution. The effect of Zn 2? and SnO 2 concentrations in deposited bath on the mechanical properties and morphological characteristics of the composite coatings were examined. The characterizations of the sample were analyzed using scanning electron microscopy couple with energy dispersive spectroscopy (SEM/EDS), X-ray diffraction (XRD) and atomic force microscopy (AFM). The electrochemical de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The particles were also found to have no chemical interaction with the matrix, and the particle content in the coating was subject to the concentration of the particle in the plating bath. However, [51] reported formation of Zn x Sn x phases when SnO 2 was codeposited with Zn. The chemical interaction observed in this work may be due to the change in operating parameters and bath formulations.…”
Section: Composition Morphological and Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The particles were also found to have no chemical interaction with the matrix, and the particle content in the coating was subject to the concentration of the particle in the plating bath. However, [51] reported formation of Zn x Sn x phases when SnO 2 was codeposited with Zn. The chemical interaction observed in this work may be due to the change in operating parameters and bath formulations.…”
Section: Composition Morphological and Structural Propertiesmentioning
confidence: 99%
“…The development of composite coatings also aims at improving this property to extend the applications of the coatings. The inclusion of reinforcement particles hinder plastic deformation due to the dispersive strengthening effect exhibited by the particles [51]. The authors also reported that the alteration of microstructure and strengthening of the coatings by formation of compact and crack-free coating add to the minimization of friction due to the presence of embedded particles The particles also form a protective barrier between the matrix and the wearing medium, thus reducing direct contact and friction coefficient [53].…”
Section: Wear Resistancementioning
confidence: 99%
“…Their usage in various industrial sectors as protective coating for large quantities of metal products and other fabricated ferrous metallic parts are enormous [13]. The service life of zinc coating can be enhanced by addition of inert materials into its coating during bath preparation [14]. This inclusion promotes advantageous characteristics for special applications such as semi-conductor, embedded system, defence and optoelectronic components [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the second‐phase particles that are used to prepare the zinc‐based composite coatings are mainly metal or non‐metal oxides which are easily incorporated into the matrix. These reported oxides include SiO 2, CuO, V 2 O 5, ZnO, Al 2 O 3, ZrO 2, TiO 2, CeO 2 , SnO 2 , etc. The corrosion current densities for zinc coatings incorporated by these oxide particles were shown to be obviously lower than that of pure zinc coating and were in the range of half to one third of the intrinsic corrosion current density of pure zinc coating.…”
Section: Introductionmentioning
confidence: 99%